Effects of modified multimodal analgesia on postoperative pain, sedation, and prognosis of gynecological patients. Issue 4 (8th December 2021) - Zhang, Fan; Luo, Man; Liu, De‐Xing; Zhu, Yu‐Hang; Zhu, Zhao‐Qiong
Abstract: Patient‐controlled intravenous analgesia is one of the most common pain relief methods in the postoperative period, but its adverse reactions remain high. This study aimed to explore the role of improved combined analgesia methods in pain, sedation, postoperative nausea, and vomiting (PONV) in patients undergoing gynecological surgeries. This study was a prospective, randomized, double‐blind controlled study. A study population of 72 patients undergoing gynecological surgery were randomly assigned to either the TAPB + S group or the TAPB + N group. All patients in both groups underwent a transversus abdominis plane block (TAPB) after induction of anesthesia. The TAPB + S group received a continuous intravenous infusion (2 ml/h) of sufentanil (1 μg/kg) plus metoclopramide (30 mg) through 100 ml elastomeric pumps postoperatively. The TAPB + N group received a continuous intravenous infusion (2 ml/h) of nalbuphine hydrochloride (1 mg/kg) plus metoclopramide (30 mg) postoperatively. The main outcome measures were as follows: postoperative pain intensity, Ramsay sedation score (RSS) after surgery, PONV occurrence rate, and rescue analgesics. The RSS of the TAPB + S group was significantly higher than that of the TAPB + N group at 2, 4, and 6 h after the operation. However, the visual analog scale score of the TAPB + S group was much higher than that of the TAPB + N group. No significant differences were found between the two groups in terms of consumption of opioids and other narcotic drugs at 2, 4, 6, 24, and 48 h after the operation. No statistically significant differences were found with respect to PONV and other adverse events in both groups. Taken together, our data indicate that the TAPB + N program can provide better postoperative analgesia and also reduce the use of strong opioids. The more optimized scheme of perioperative analgesia still needs to be researched further. Abstract : In this study, a randomized‐controlled clinical study was carried out to evaluate the effects of transversus abdominis plane block combined with opioid‐reducing anesthesia and analgesia on the prognosis of gynecological patients with the aim of optimizing clinical anesthesia management.